Pengunaaan Analisis Rasio dalam Pengukuran Kinerja Keuangan Perusahaan pada PT. Gudang Garam Tbk - Sayekti Suindah Dwiningwarni; Judi Suharsono; Dian Yuliana Safitri (Jurnal Riset Inspirasi Manajemen dan Kewirausahaan, 2019)
The motivation of this research is research (Rosini & Gunawan 2018; B.Batchimeg 2017). In addition, the motivation of this study also continued the research of Sayekti Suindyah Dwiningwarni (1997). The purpose of this study (1) to analyze the development of corporate financial performance from solvency and profitability ratios; (2) to analyze the measurement of the company's financial performance using solvency and profitability ratios. This research uses quantitative descriptive analysis method.The results of the study (1) the development of the company's financial performance in terms of solvency ratios experienced good development, this is indicated by the value of the solvency ratio that is getting better / better in fulfilling both short and long term obligations; (2) the development of the company's financial performance in terms of profitability ratios from experiencing good development, this is indicated by the value of the profitability ratio that is getting better / better in generating profits or profits; (3) measurement of company performance in terms of solvency ratio shows solvable conditions, meaning the assets is greater than the debt. (4) measurement of company performance in terms of profitability ratios shows good conditions, meaning the level of profits obtained from year to year has increased. This means that the company is in good financial condition and sovabel.